2014
DOI: 10.2478/s13545-014-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on physiology and bioenergetics of adult Harris mud crab Rhithropanopeus harrisii (Gould, 1841) from the southern Baltic Sea

Abstract: Rates of physiological processes and bioenergetics of the Harris mud crab Rhithropanopeus harrisii were determined during a 7-day experiment on adult males (mean wet weight 0.83 ± 0.16 g) exposed to temperatures of 15ºC and 20ºC (S = 7). The results show that the change in temperature by 5ºC caused detectable changes in locomotor activity, food consumption and faeces production and significant (p < 0.05) changes in metabolic rates. Food assimilation efficiency and the ammonia excretion rate did not change sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Our study demonstrated that temperature plays an important role in modulating the effects of the invasive mud crab R. harrisii on native F. vesiculosus stands and associated invertebrates in the northeastern Baltic Sea. The impact of the crab was more pronounced at higher temperatures, suggesting that the presence of the invader has negative consequences for native invertebrate species, particularly under summer conditions when the metabolic demands and food intake requirements of the invader are higher [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that temperature plays an important role in modulating the effects of the invasive mud crab R. harrisii on native F. vesiculosus stands and associated invertebrates in the northeastern Baltic Sea. The impact of the crab was more pronounced at higher temperatures, suggesting that the presence of the invader has negative consequences for native invertebrate species, particularly under summer conditions when the metabolic demands and food intake requirements of the invader are higher [49].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the round goby retained most of its amphipod feeding activity in a colder environment. Such temperature-induced differences in feeding may reflect the more southerly origin of round goby compared with mud crab (Lee & Johnson, 2005; Hegele-Drywa & Normant, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Water temperature affects species' metabolic demands and predation rates (Lee & Johnson, 2005) with maximum feeding rates coinciding with the species' thermal optimum (Iacarella et al , 2015). Temperature optima for the more southern round goby and the more northern mud crab are recorded at 26 and 20°C, respectively (Lee & Johnson, 2005; Hegele-Drywa & Normant, 2014). Thus, temperature may set interaction strength among invasive predators, modify predation rates through species-specific temperature-consumption responses and thereby define overall impacts of novel predators on local benthic invertebrate communities (Oyugi et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation